Computational study of PCM cooling for electronic circuit of smart-phone. (2021) - Kurhade, Anant; Talele, Virendra; Venkateswara Rao, T.; Chandak, Archana; Mathew, V.K.
Abstract: Smartphone's functional use is versatile in a modern-day application, which causes a prone in electronics performance; this is mainly due to gamming, high power camera applications, and increased usage of the internet. The continuous usage causes high power dissipation level in smartphones to increase by about 2–6 W. Depending on the scale of application, the cooling strategy is used in smartphones. In the present paper, a passive phase change material cooling strategy is proposed which can utilize the advantage of isotopic heat conduction from the electronic element. It changes its phase from solid to liquid to give an optimum cooling strategy over the electronic element which help in keeping the temperature of the electronic element below 85 °C. The economic mid-range customer segment smartphones are embedded with cooling strategy such as natural convection, indirect heat-pipe cooling and forced convection which typically fails for high power usage applications.